1985
DOI: 10.1056/nejm198508013130502
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Deposition of Eosinophil-Granule Major Basic Protein in Atopic Dermatitis

Abstract: Although blood eosinophilia is commonly present in atopic dermatitis, accumulation of tissue eosinophils is not prominent. To determine whether eosinophil degranulation occurs in lesions of atopic dermatitis, we analyzed tissues by immunofluorescence for the presence of the eosinophil-granule major basic protein. Twenty biopsy specimens from 18 patients with atopic dermatitis were studied, and all showed major basic protein staining outside eosinophils. In 18 specimens, the staining was fibrillar, was located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
171
0
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(180 citation statements)
references
References 29 publications
7
171
0
2
Order By: Relevance
“…9 Assessment of eosinophil involvement in disease should not be based simply on the number of eosinophils present because intact eosinophils may not be evident; i.e., tissues should be examined for evidence of eosinophil degranulation. 23,24 Hematoxylin and eosin staining often fails to show the presence of eosinophil granules and extracellular granule proteins. Previous studies on cardiac tissue have shown the advantages of immunofluorescence staining over light microscopy for accurately visualizing eosinophils and their granules or extracellular proteins (Chau E and others, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Assessment of eosinophil involvement in disease should not be based simply on the number of eosinophils present because intact eosinophils may not be evident; i.e., tissues should be examined for evidence of eosinophil degranulation. 23,24 Hematoxylin and eosin staining often fails to show the presence of eosinophil granules and extracellular granule proteins. Previous studies on cardiac tissue have shown the advantages of immunofluorescence staining over light microscopy for accurately visualizing eosinophils and their granules or extracellular proteins (Chau E and others, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Prior studies of diseased tissues have shown extensive MBP deposition in the absence of intact tissue eosinophils. 23,24 By using an immunofluorescence technique for the colocalization of eosinophil granule MBP and P. brasiliensis, we tested the hypothesis that eosinophil infiltration and degranulation regularly occur in tissues from patients with paracoccidioidomycosis.…”
mentioning
confidence: 99%
“…In some patients the eosinophil infiltrate was not found by hematoxylin-eosin staining, since cells were completely degranulated and seen only by means of immunohistochemistry or electron microscopy. Accordingly, significant deposits of eosinophil-derived MBP and EDN/EPX could be detected in the eczematous skin of patients by immunohistochernical techniques, as a sign of eosinophil degranulation at the site of inflammation (22,23), Moreover, a correlation between disease activity and deposition of eosinophil granule content could be suggested (23), Late-phase reactions Similar findings were obtained in investigating the "late-phase reaction" (LPR) upon provocation with allergens by the skin chamber technique (6), Because of the mode of induction, however, the pattern of eosinophil-derived granule proteins is comparable with, but not identical to, findings in patients with AD, Nevertheless, the experimental LPR, as a model system, represents a useful tool for a better understanding of pathophysiologic principles which may also be important in AD (23), Hence a significant infiltration of basophils and, particularly, of eosinophils in the skin was detected, characteristically within 6-8 h after local allergen challenge, A mononuclear cellular infiltrate was detected after almost 24 h. During this interval most of the eosinophils were degranulated or even completely destroyed (6,23). As reported recently, a significant increase in the number of activated, EG2-positive eosinophils was observed in LPRs of nasal mucosa within 24 h following intranasal challenge of patients with allergic rhinitis with Phleum pratense (8), Moreover, these findings correlated significantly with the expression of mRNA for Th2 cytokines, particularly for lL-5.…”
Section: Eosinophilic Granulocytes and Admentioning
confidence: 99%
“…2,3 Eosinophils are sparse, although eosinophil products (major basic protein) are prominent. 4 Although the pathogenic role of allergy in AD has been debated for over a century, clinical studies over the past 2 decades have supported the pathogenic role of food allergy in a subset of patients with AD. [5][6][7] A recent study found that approximately 40% of children with moderate-to-severe AD attending a university dermatology clinic had food hypersensitivity.…”
mentioning
confidence: 99%